E‐CHAIM as a Model of Total Electron Content: Performance and Diagnostics - D. R. Themens; Ben Reid; P. T. Jayachandran; Bion Larson; A. V. Koustov; Sean Elvidge; A. M. McCaffrey; Chris Watson (Space Weather)
Abstract Here, we assess to what extent the Empirical Canadian High Arctic Ionospheric Model (E‐CHAIM) can reproduce the climatological variations of vertical Total Electron Content (vTEC) in the Canadian sector. Within the auroral oval and polar cap, E‐CHAIM is found to exhibit Root Mean Square (RMS) errors in vTEC as low 0.4 TECU during solar minimum summer but as high as 5.0 TECU during solar maximum equinox conditions. These errors represent an improvement of up to 8.5 TECU over the errors of the International Reference Ionosphere (IRI) in the same region. At sub‐auroral latitudes, E‐CHAIM RMS errors range between 1.0 and 7.4 TECU, with greatest errors during the equinoxes at high solar activity. This represents an up to 0.5 TECU improvement over the IRI during summer but worse performance by up to 2.4 TECU during the winter. Comparisons of E‐CHAIM performance against in situ measurements from the European Space Agency's Swarm mission are also conducted, ultimately finding behavior consistent with that of vTEC. In contrast to the vTEC results, however, E‐CHAIM and the IRI exhibit comparable performance at Swarm altitudes, except within the polar cap, where the IRI exhibits systematic underestimation of electron density by up to 1.0 × 1011 e/m3. Conjunctions with mid‐latitude ionosondes demonstrate that E‐CHAIM's errors appear to result from compounding same‐signed errors in its NmF2, hmF2, and topside thickness at these latitudes. Overall, E‐CHAIM exhibits strong performance within the polar cap and auroral oval but performs comparably to the IRI at sub‐auroral latitudes.